Preparation，Microstructure and Properties of Copper Matrix Protective Coatings for Blast Furnace Tuyere - QIAO En-tao, WANG Zhou-fu, MA Yan, LIU Hao, WANG Xi-tang (Cailiao Baohu, 2023)
In order to prolong the effective service life of blast furnace tuyeres，a protective coating was prepared on the surface of pure copper substrate by embedding co-infiltration method using pure copper plate as base material，NH4 Cl as infiltration catalyst，and nickel，iron and aluminum as main components of co-infiltration agent.The effects of infiltration agent content，co-infiltration agent ratio and holding time on the protective coating and coating/substrate interface structure were studied.The phase composition and microstructure of the as-prepared coatings were characterized by XRD，SEM and EDS，and the micro-Vickers hardness of the coatings was evaluated.Results showed that by adjusting the content of NH4Cl catalyst and the ratio of Ni: Fe: Al in co-infiltration agent，a coating metallurgically bonded to the pure copper substrate could be prepared after heat treatment.After the aluminum element penetrated into the copper matrix，the formed infiltration layer had an obvious gradient structure，which significantly improved the micro-Vickers hardness of the material.The existence of “high aluminum phase”in the infiltration layer hindered the dislocation movement of the copper matrix and further improved the microhardness of the material.blast furnace tuyere；pure copper；embedded co-infiltration；coating；microhardness